An Experimental Study of Nozzle Temperature and Heat Treatment (Annealing) Effects on Mechanical Properties of High‐Temperature Polylactic Acid in Fused Deposition Modeling. Issue 5 (10th February 2020) - Akhoundi, Behnam; Nabipour, Mojtaba; Hajami, Faramarz; Shakoori, Diana
Abstract : Fused deposition modeling (FDM) is the trendiest three‐dimensional (3D) printing method among additive manufacturing technologies. In this process, the final parts are constructed through layer‐by‐layer adhesion of thermoplastic polymers. Amorphous thermoplastic polymers have better printability compared to semicrystalline ones; so, they are most popular with FDM users. Generally, the overall mechanical properties of FDM 3D printed parts are weaker in comparison to the traditional methods (such as injection molding) due to the weak bonds between the deposited rasters and layers. Therefore, the introduction of new materials with higher mechanical properties and easy printing process of the semicrystalline polymers has always been challenging to progress the mechanical properties of the products. In this study by the FDM process, the effect of nozzle temperature and heat treatment (annealing) on the mechanical properties of high‐temperature polylactic acids is investigated. The increase in the nozzle temperature develops the rasters and layers bonding, and the heat treatment of the parts after printing rises the crystallinity percentage, which is crucial for the improvement of mechanical properties. Experimental results show that an increase in the nozzle temperature raises the tensile strength and modulus to 65.7 MPa and 4.97 GPa, respectively. Furthermore, the heat treatment process increases the tensile strength and modulus up to 67.4 MPa and 5.65 GPa. The final tensile modulus values are the highest ones reported for pure materials printed by the FDM process. POLYM. ENG. SCI., 60:979–987, 2020. © 2020 Society of Plastics Engineers